Reproductive Performance of Nile Tilapia (Oreochromis Niloticus Linnaeus, 1758) Fed on Periphyton and Rice Bran in Gemena City (Sud-Ubangi Province) in Democratic Republic of the Congo - A.G. Kongbo; F.K. Mukonga; F.N.U. Nyongombe; M. Monizi; K.N. Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2024)
The overall aim of this study was to evaluate the reproductive performance of Oreochromis niloticus reared in ponds fed with periphyton and rice bran. It was carried out using a database resulting from an experiment carried out in the Gemena town hall, South Ubangi province in the Democratic Republic of Congo with Oreochromis niloticus fry fed on periphyton and rice bran. The methodological approach consisted of sampling the physico-chemical parameters of the pond water and the reproductive parameters, in particular the gonado-somatic ratio (GSR), the condition factor (K), fecundity and oocyte size. After analysis by pond category, it was found that the two treatments differed in terms of gonado-somatic ratio and condition factor. Treatment T1 is characterised by a relatively better value (RGS varying from 0.35 to 5.03 and K varying from 0.47 to 6.75) than treatment T0 (RGS varying from 0.34 to 3.91 and K varying from 0.20 to 3.26). The absolute fecundity of Oreochromis niloticus in the ponds with rice bran and those with periphyton varied respectively from 216-1504 and 279-1570. In contrast, the relative fecundity was 3.17-15.7 for the ponds with rice bran and 5.49-17.2 for the ponds with periphyton. These values correspond to total lengths of 11.6-18.1 Cm and 14.6-22.2 Cm, respectively. Oocyte diameter ranged from 0.95-2.00 mm, with an average of 1.63±0.05 mm, and from 0.89-2.15 mm, with an average of 1.59±0.05 mm, for females from ponds with rice bran and those with periphyton, respectively. At the end of this study, the results obtained showed that the females fed with periphyton showed a higher relative fecundity than those fed with rice bran. The data collected on the reproductive parameters indicate better reproductive performance in ponds fed with periphyton than in ponds fed with rice bran.